Islamic Corporate Social Responsibility, Leverage And Liquidity On Financial Performance Moderated By Company Size - Luluk Ul Fatul Diroh; Mochlasin Mochlasin (LPPM ISNJ Bengkalis, 2023)
Financial performance has a vital role in the company; good financial performance can positively impact the company. This study examines and demonstrates the influence of Islamic corporate social responsibility (ICSR), leverage, and liquidity on financial performance, which is moderated by firm size. The research population is a company registered in the Jakarta Islamic Index 30 (JII 30) for 2017-2021. The sample of this research is ten companies obtained from the purposive sampling method. The data analysis technique uses Moderated Regression Analysis (MRA). Financial performance is measured using return on assets (ROA), leverage using the debt to equity ratio (DER), liquidity is proxied by the current ratio (CR), and ICSR is measured using several predetermined indicators. The results showed that ICSR has no impact on financial performance, leverage has a significant positive impact on financial performance, and liquidity has a significant negative impact on financial performance. Company size cannot moderate the impact of ICSR on financial performance, but company size can moderate the impact of leverage and liquidity on financial performance. This research can complement existing theories and research results. It can be a reference for companies in improving and enhancing their performance, as well as for investors to evaluate company performance to obtain certainty in investment.